The influence of signal attributes on the willingness to pay for pasture-raised beef - Chini, Juliana; Spers, Eduardo Eugenio; Ribeiro da Silva, Hermes Moretti [UNESP]; Jejcic de Oliveira, Mirella Cais (Univ Sao Paulo, Fac Economia, 2020)
Purpose - This study aims to identify the marginal impact of introducing a signal attribute of pastureraised beef on consumer willingness to pay (WTP) for other independent attributcz. Design/methodology/approach - The study is divided into two steps. The first, qualitative, consisted of investigating the values consumers have regarding beef production. To this end, 52 interviews with Brazilian and US consumers were conducted using laddering. In the second, quantitative, six experiments, (face to face and online) with 267 consumers of beef were performed. Findings - As a result, the main value found for the Brazilians was security, while for the Americans was self-direction. For consumers, the WTP for animal welfare was the most important in the choice experiments where this information was present. Originality/value - These findings offer an alternate beef differentiation, enabling it to be sold with higher added value by integrating these.
Keywords: Experiment; Consumer; Beef; International marketing; Attributes